Dynamics underlying Plasmodium vivax mitochondrial genome diversity across the Eastern Hemisphere - Raijmakers, L (2018)
Plasmodium vivax (Pv) malaria is a human infecting blood parasite distributed widely across both tropical and temperate regions. In order to increase the understanding of past dynamics influencing its current distribution, this thesis explores its origins, spread and evolutionary past through diversity and evolution of the mitochondrial genome. Exploring several different factors that would have affected its dispersal, including mosquito vector species and geographic distance, the main focus of Chapter 2 is on understanding when and with which past human migrations it spread across the continents of the Eastern Hemisphere. A special emphasis on the Melanesian region is included in Chapter 3, which shows considerable diversity in human populations and cultures, and has high incidence of all four species of human infecting malarias (P. vivax, P. falciparum, P. malariae, P. ovale). Although previous publications indicated an especially high level of diversity in Pv mitochondrial genomes in Melanesia; in this study it is shown to be a sampling artefact due to denser sampling. In both chapters a novel cross-disciplinary data comparison is undertaken, matching Pv mitochondrial genome phylogeny and population genetics with modern human mitochondrial genome data, human and hominid archaeological data, archaeological data from human commensal species and phylogenetic data from human associated diseases. Results indicate that not only the current Melanesian Pv but also the Pv strains found across the Asian continent to the east of India were likely introduced by the first wave of anatomically modern humans (Homo sapiens) to leave Africa. The strong patterning seen across this eastern region has ostensibly been shaped not only by relatively stable human populations for the last several thousand years, but is also associated with a strong regional heterogeneity of mosquito vector species and clades. In contrast, the present study confirms previously observed homology in Pv mitochondrial genetics from India to the west. Presumably the homology is due to increased human population movement and contact between the western regions, as well as greater overlap in mosquito vector species across the region, as shown in this study. Even so, with the addition of data from new sites across the western half of the Eastern Hemisphere, including samples from central and western Asia, there is a detection of low levels of population diversity. Lastly, Chapter 4 gives an overview of the applications of different genetic markers used in malaria research over time, reviewing the continued value of using mitochondrial DNA, on its own and in combination with other available genetic data – in an age of whole genome sequencing.